DEVELOPMENT STRATEGY FOR SMALL AND MEDIUM ENTERPRISES (SME) BASED ON SUNDA CULTURE IN CIBADUYUT FOOTWEAR INDUSTRY - Yuyun Yuniarti; Yuyun Yuningsih; Umi Hani; Sumardani Sumardani (SAMPURASUN, 2022)
Cibaduyut footwear industry is one of the industries that produce products various kinds of footwear such as sandals, shoes, shoes, shoes or casual shoes, which are the main raw material is leather. In carrying out its business activities the footwear industry. Cibaduyut faces several obstacles, especially those concerning manufacturing or processes financial production and management, especially concerning financial records. Rapi dan perfectly complies with financial management standards, besides other obstacles is that businesses cannot develop shoe based products to the application of Sudanese cultural values ​​that are famous for the concept of Silih Asah, Silih compassion, foster care, this turned out to weaken the competitiveness of footwear products on the scene International. The research method used in this study is a qualitative method using descriptive analysis, the data collection method used is a method direct observation (observation), in-depth interviews (in-depth interview) as well direct interviews with several informants, and using triangulation and snowball sampling. Based on the results of the study showed that the marketing strategy carried out by Cibaduyut footwear perpetrators of the city of Bandung based on Sudanese culture, stating, foster care still experiences several obstacles, especially in the supplier is still in nature traditional so that it cannot yet be competitive globally.